High‐Affinity Dimeric Aptamers Enable the Rapid Electrochemical Detection of Wild‐Type and B.1.1.7 SARS‐CoV‐2 in Unprocessed Saliva. (4th October 2021) - Zhang, Zijie; Pandey, Richa; Li, Jiuxing; Gu, Jimmy; White, Dawn; Stacey, Hannah D.; Ang, Jann C.; Steinberg, Catherine‐Jean; Capretta, Alfredo; Filipe, Carlos D. M.; Mossman, Karen; Balion, Cynthia; et al.
Abstract: We report a simple and rapid saliva‐based SARS‐CoV‐2 antigen test that utilizes a newly developed dimeric DNA aptamer, denoted as DSA1N5, that specifically recognizes the spike proteins of the wildtype virus and its Alpha and Delta variants with dissociation constants of 120, 290 and 480 pM, respectively, and binds pseudotyped lentiviruses expressing the wildtype and alpha trimeric spike proteins with affinity constants of 2.1 pM and 2.3 pM, respectively. To develop a highly sensitive test, DSA1N5 was immobilized onto gold electrodes to produce an electrochemical impedance sensor, which was capable of detecting 1000 viral particles per mL in 1:1 diluted saliva in under 10 min without any further sample processing. Evaluation of 36 positive and 37 negative patient saliva samples produced a clinical sensitivity of 80.5 % and specificity of 100 % and the sensor could detect the wildtype virus as well as the Alpha and Delta variants in the patient samples, which is the first reported rapid test that can detect any emerging variant of SARS‐CoV‐2. Abstract : Rapid and simple: an electrochemical sensor, based on a high‐affinity dimeric DNA aptamer for the SARS‐CoV‐2 spike protein was developed to detect the wildtype and Alpha and Delta variant in unprocessed saliva samples in 10 minutes, providing a detection limit of 1000 copies mL −1, clinical sensitivity of 80.5 % and specificity of 100 %.